Sistem Deteksi Jatuh dan Peringatan Dini Pada Manusia Berbasis Android - Ade Hendi; Hermanto Hermanto; Abdur Rozaaq (STMIK Budi Darma, 2022)
Falling is an event that has often happened to humans in the surrounding environment, and almost every human being has experienced a fall. The condition of falling in humans can have very serious effects, such as injuries and may even increase the risk of death. The cause of death due to a fall can be caused by several factors, including the weakness of a person's ability to stand back up after a fall, when he falls there is no first aid, someone who falls has difficulty contacting his family or closest people. The purpose of this study is to build a fall detection system in humans. This system utilizes the accelerometer sensor on a smartphone to detect human movement. The fall detection system can run with various conditions of falling motion position with an accuracy level of 87.27% from a total of 110 trials, and a sensitivity of 77.5% so it is properly to use in detecting falling motion.